MANIFESTASI NEUROPSIKIATRIK PADA LUPUS ERITEMATOSUS SISTEMIK DI RSUD DR. SOETOMO SURABAYA - Nadya Rinda Eka Rana; Awalia Awaliah; Yetti Hernaningsih; Hanik Badriyah Hidayati (NEURONA, 2019)
NEUROPSYCHIATRIC MANIFESTATION AMONG SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS IN GENERAL HOSPITAL SURABAYAABSTRACTIntroduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease with unknown causes and extensive clinical manifestations and diverse disease pathways. The clinical manifestations of SLE are very diverse, including the involvement of the nervous system and psychiatric syndrome (neuropsychiatric).Aims: To describe clinical neuropsychiatric manifestations of   patients with SLE in Soetomo General Hospital Surabaya.Methods: This was a cross-sectional study based on medical record data on all SLE patients treated at Dr. Soetomo Hospital Surabaya, from January-December 2017. Neuropsychiatric manifestations assessment were based on the nomenclature of the American College of Rheumatology (ACR) in 1999.Results: There were 49 patients, mostly women (98%) with mean age 30,8±10,2 years old. Neurological manifestation was the 3rd  most common diagnosis (43%) after hematologic disorder (73.5%) arthritis (53.1%). The manifestations of neuropsychiatric manifestation were mainly seizures (40.8%), headache (34.7%), cerebrovascular disease (26.5%), acute confusional state (20.4%), cognitive dysfunction (6.1%), and polyneuropathy (8.2%).Discussion: The most common neuropsychiatric clinical features in SLE patients are seizures, headache, cerebrovascular disease, and acute confusional state.Keywords: Lupus neuropsychiatry, prevalence, systemic lupus erythematosusABSTRAKPendahuluan: Lupus eritematosus sistemik (LES) merupakan penyakit inflamasi autoimun kronik yang belum diketahui penyebabnya dengan perjalanan penyakit yang luas. Manifestasi klinis LES sangat beragam, antara lain keterlibatan sistem saraf dan sindrom psikiatri (neuropsikiatri).Tujuan: Untuk mengetahui manifestasi neuropsikiatrik pasien dengan LES di RSUD Dr. Soetomo, Surabaya.Metodologi: Penelitian potong lintang berdasarkan data rekam medik terhadap semua pasien LES yang dirawat di RSUD Dr. Soetomo, Surabaya, pada bulan Januari hingga Desember 2017. Manifestasi neuropsikiatrik dinilain berdasarkan nomenklatur American College of Rheumatology (ACR) tahun 1999.Hasil: Didapatkan 49 subjek yang hampir semuanya (98%) adalah perempuan dengan rerata usia 30,8±10,2 tahun. Gangguan neurologis merupakan ketiga tersering (43%) setelah gangguan hematologi (73,5%) dan artritis (53,1%). Manifestasi neuropsikiatri terutama kejang (40,8%), nyeri kepala (34,7%), penyakit serebrovaskular (26,5%), keadaan konfusi akut (20,4%), dan polineuropati (8,2%).Diskusi: Manifestasi klinis neuropsikiatri yang paling banyak dialami oleh pasien LES adalah kejang, nyeri kepala, penyakit serebrovaskular, dan keadaan konfusi akut.Kata kunci: Lupus eritematosus sistemik, manifestasi klinis, neuropsikiatri